Headache in the presentation of noncephalic acute illness - Tzadok, Tomer (J Neurosci Rural Pract, 2015)
BACKGROUND: Headache is a frequent symptom of many systemic diseases that do not involve cranial structures. In this observational study, we assessed factors associated with headache in the acute presentation of systemic conditions in a nonsurgical emergency department (ED). METHODS: Consecutive patients, admitted to Soroka University Medical Center ED due to noncephalic illness, were prospectively surveyed using a structured questionnaire focused on the prevalence and characteristics of headache symptoms. Medical data were extracted from the patient's charts. RESULTS: Between 1 and 6/2012, 194 patients aged 64.69 ± 19.52 years, were evaluated. Headache was reported by 83 (42.7%) patients and was more common among patients with febrile illness (77.5% vs. 22.5%, P < 0.001). Respiratory illness and level of O(2) saturation were not associated with headache. Headache in the presentation of a noncephalic illness was associated with younger age (58 vs. 69, P < 0.001) and with suffering from a primary headache disorder (48.2% vs. 10.8%, P < 0.001). Headache was also associated with higher body temperature and lower platelets count. CONCLUSIONS: Headache is a common symptom in acute noncephalic conditions and was found to be associated with younger age and febrile disease on presentation. Patients who present with primary headache disorders are more prone to have headache during acute illness. Acute obstructive respiratory disease, hypercarbia or hypoxemia were not associated with headache.